An overview: Mechanical and wear properties of hdpe polymer nanocomposites reinforced with treated/non-treated inorganic nanofillers - Ahmed, T. (Springer Science and Business Media Deutschland GmbH, 2020)
Recently, several review papers on the topic of polymer nanocomposites have been written. Specifically, the scope of this article is aimed to include mechanical and tribological properties of reinforced high-density polyethylene owing to correlation of such properties in engineering and science applications. This paper provides reconsideration of mechanical and tribological properties of HDPE polymer nanocomposites reinforced with treated and non-treated inorganic nanofillers focusing on CaCO3, SiO2, and nano clay. Some fundamental concepts and certain contradictions to the established facts are narrated. Moreover, classifications, comparisons, and the factors necessary for consideration of properties of HDPE are included as well. Â© Springer Nature Singapore Pte Ltd 2020.